Health, growth and reproductive success of mice exposed to environmentally relevant levels of Ra-226 via drinking water over multiple generations. (July 2015) - Walsh, Stephanie; Satkunam, Meloja; Su, Ben; Festarini, Amy; Bugden, Michelle; Peery, Harry; Mothersill, Carmel; Stuart, Marilyne
Abstract Purpose: To assess health, growth and reproductive success of mammals exposed for multiple generations to levels of radium-226 known to occur in environments surrounding uranium mines and mills in Canada. Methods: The study consisted of a control group and four treatment groups each containing 40 mice (20 males and 20 females) of the CBA/CaJ strain that were continuously exposed to a range of radium-226 levels via drinking water. Breeding was at 8–10 weeks of age and the study was concluded after three breeding cycles. Results: When compared to control mice, constant consumption of drinking water containing 0.012, 0.076, 0.78 and 8.0 Bq/l of radium-226 over four generations of mice did not demonstrably affect physical condition, weight, pregnancy rate, number of pups per litter, sex ratio and bodyweight gain of pups. Between generations, the observed differences in pregnancy rates that were noted in all groups, including controls, seemed to directly correlate with the weight and age of the females at breeding. Conclusions: Based on the endpoints measured on four generations of mice, there is no indication that the consumption of radium-226 via drinking water (at activity concentrations up to 8.0 Bq/l) affects health, growth and reproductive fitness.